Family planning and child survival : 100 developing countries. [John A. Ross ... et al.]. New York : Center for Population and Family Health, Columbia University, 1988 - Juárez, Fátima (Estudios Demográficos y Urbanos, 1990)
Family Planning and Chiid Survival. 100 Developing Countries, Center for Population and Family Health, Columbia University, New York, USA, 1988.